2009
DOI: 10.1080/10837450902814164
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation ofSan-huangdispersible tablet – an efficient delivery system for Traditional Chinese Medicine

Abstract: San-huang dispersible tablet (SHDT) was designed with a patented technology to enrich the active ingredients in rhubarb and with a wide selection of excipients in the new manufacturing procedure. The total rhubarb anthraquinones were first enriched in the extract by our patented technology. Eudragit L100, S100 and PEG-6000 were used to release a part of the total rhubarb anthraquinones at the colon to induce the cathartic effect of the anthraquinones by another patented technology. Microcrystalline Cellulose (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…A dispersible tablet of San‐huang , composed of the three herbs baicalin, emodin and berberine hydrochloride, was prepared to improve their dissolution. The results of a dissolution test in 900 ml of 0.05% sodium dodecyl sulfate demonstrated that the dissolution of the baicalin was more than double that of the San‐huang tablet, but the bioavailability in vivo has not yet been reported . A baicalin–phospholipid complex was prepared to improve the bioabsorption of baicalin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A dispersible tablet of San‐huang , composed of the three herbs baicalin, emodin and berberine hydrochloride, was prepared to improve their dissolution. The results of a dissolution test in 900 ml of 0.05% sodium dodecyl sulfate demonstrated that the dissolution of the baicalin was more than double that of the San‐huang tablet, but the bioavailability in vivo has not yet been reported . A baicalin–phospholipid complex was prepared to improve the bioabsorption of baicalin.…”
Section: Introductionmentioning
confidence: 99%
“…The results of a dissolution test in 900 ml of 0.05% sodium dodecyl sulfate demonstrated that the dissolution of the baicalin was more than double that of the San-huang tablet, but the bioavailability in vivo has not yet been reported. [9] A baicalin-phospholipid complex was prepared to improve the bioabsorption of baicalin. A pharmacokinetic study in eight rats after oral intake of baicalin and its phospholipid complex showed the mean areas under the concentration-time curves (AUC) were 4.9 and 14.6 mg h/ml, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] showed no significant endogenous peaks interfering with any of all analytes or IS at the retention times under the described chromatographic conditions. Calibration curves of the five analytes showed good linearity with correlation coefficients greater than 0.9983 in relatively wide dynamic concentration ranges.…”
Section: Methods Validationmentioning
confidence: 99%
“…Briefly, 3 kg of rhubarb medicinal materials was extracted by 30% ethanol for three times using the described method to obtain rhubarb total free AQs [4]. 28 g of rhubarb total free AQs was sieved and mixed with MCC, PEG-6000 and fixed amount of aqueous solvent containing 2% (w/v) PEG-6000 and 2% (w/v) HPMC.…”
Section: Rtfa-ocdd-gn Preparationmentioning
confidence: 99%
See 1 more Smart Citation